2023
DOI: 10.3390/plants12091768
|View full text |Cite
|
Sign up to set email alerts
|

Extracts and Residues of Common Ragweed (Ambrosia artemisiifolia L.) Cause Alterations in Root and Shoot Growth of Crops

Abstract: Following the novel weapon hypothesis, the invasiveness of non-native species, such as common ragweed (Ambrosia artemisiifolia L.) can result from a loss of natural competitors due to the production of chemical compounds, which negatively affect native communities. Particularly the genus Ambrosia produces several types of organic compounds, which have the potential to inhibit germination and growth of other plants. Subsequent to an assessment of the chemical content of three different ragweed extracts (aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In a very recent paper (Hall et al, 2023, submitted for publication), a sophisticated design provided more detailed results on the effects of high temperature on the survival rates of ragweed seeds. The authors found that wet seeds were in general more sensitive to any heat treatment than dry seeds.…”
Section: Starfinger and S €mentioning
confidence: 99%
“…In a very recent paper (Hall et al, 2023, submitted for publication), a sophisticated design provided more detailed results on the effects of high temperature on the survival rates of ragweed seeds. The authors found that wet seeds were in general more sensitive to any heat treatment than dry seeds.…”
Section: Starfinger and S €mentioning
confidence: 99%